Behavioural patterns in allergic rhinitis medication in Europe - Sousa-Pinto, Bernardo (2022)
Funding: This study was funded by ARIA. MASK-air® has been supported by EU grants (EU Structural and Development grant, POLLAR: EIT Health and Structural and Development Funds) and educational grants from Mylan-Viatris, ALK, GSK, Novartis and Uriach. Open Access funding enabled and organized by Projekt DEAL.